Terahertz wave propagation in single-walled carbon nanotube reinforced polymer nanocomposite. (2014) - Narendar, S.
Polymer nanocomposites are an important class of nanomaterials with potential applications including but not limited to structural and cushion materials, electromagnetic and heat shields, conducting plastics, sensors, and catalysts for various chemical and bio processes. The present work deals with the terahertz wave propagation in single walled carbon nanotube (SWCNT) reinforced polymer nanocomposite. The SWCNT is modelled as an Euler-Bernoulli beam and the surrounding polymer is modelled as an elastic medium like linearly distributed springs. In the present formulation scale effects are also considered. Terahertz wave propagation analysis is carried out on this system and it has been found that in the presence of the polymer matrix the frequency band gap of the wave mode increases, that means it leads to a cushioning effect to the SWCNT. The wave velocity increases with the stiffness of the surrounding elastic medium.